Aspectuality and Variability of Verbal Phraseological Units in Russian Language and Speech - E. Ya. Titarenko; Yu. Yu. Balatskaya (Научный диалог, 2022)
The article deals with the problems of classification of verb phraseological units and their variants in the Russian language. Formalized criteria for the differentiation of phraseological variants depending on their syntactic and derivational structure are presented on the example of Russian verbal phraseological units. The criteria are based on the grammatical features of verbs, which are the core component of phraseological units, such as aspect and phase, taking into account the theoretical provisions of modern Slavic aspectology on the correlation and derivation of verbs. The work was done at the intersection of phraseology and aspectology, its results have both theoretical and practical significance, in particular, for clarifying the lexicographic description of Russian verbal phraseological units. More than 4,000 verbal phraseological units and more than 10,000 actual contexts in which these phraseological units and their variants are used served as the material for the analysis. The authors proposed criteria for distinguishing phraseological variants (grammatical, lexico-grammatical and lexical) and phraseological synonyms based on the morphological features of verbs (the semantics of aspect and phase), lexical composition and syntactic structure of phraseological units. The phase valence and “creative potential” of verbal phraseological units are shown, which serves as a potential source of replenishment of the phraseological fund of the Russian language.